"Celebrities at A.Y.P. who favor woman suffrage," Votes for Women, October 1909 - The Seattle Public Library (1909)
An article concerning the famous politicians and citizens that will be in attendance at the A.Y.P.E. that are in favor of women's suffrage. President Taft is cited as the most famous example. Provides quotes from politicians from suffrage states such as Utah and Idaho indicating the value of suffrage. Is a part of Votes for Woman, official organ of the Washington Equal Suffrage Association. Illustrated.